Ανάπτυξη κώδικα για την αποτύπωση των δυνατοτήτων επιθεώρησης πλοίων - Μπαμπανιώτης, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2016)
The aims of the present thesis is the evaluation of the depth of corrosion on several structural elements of a ship, as well as the calculation of the probability of failure of three different Life Saving Appliances (LSA), both based on Risk Based Inspection (RBI). The estimation of both above-mentioned models has been accomplished by developing codes in Matlab and Octave programs. Initially, the present study investigates the procedures of traditional inspections of a ship, elaborating their types and defining the organizations which operate them. After the determination of the basic parameters that constitute the RBI, the procedures of Formal Safety Assessment (FSA) are described, by the gradual application of five steps; hazard identification, risk analysis (assessment), risk control options, cost benefits analysis, and decision making. Additionally, according to the FSA, the steps which are needed to be followed are described for the implementation of an RBI procedure. Then, the phenomenon of corrosion is approached, with detailed information associated with corrosion types and preventing measures, as well as corrosion’s significance in maritime. Following the theoretical framework of corrosion, the applied model of the depth of corrosion is described. Afterwards, the thesis mentions the necessity of existence of LSA on vessels, the significance of appropriate maintenance, the several types of LSA on ships, as well as the equipment of ships with LSA according to the regulations. Subsequently, the applied theoretical model for the evaluation of the probability of failure is described, for the several types of LSA. Afterwards, the thesis presents and annotates the results of the various applications, as they have eventuated for each model. Finally, conclusions and proposals for further study are mentioned.